Strength of Footing with Punching Shear Preventers - Sang-Sup Lee; Jiho Moon; Keum-Sung Park; Kyu-Woong Bae (The Scientific World Journal)
The punching shear failure often governs the strength of the footing-to-column connection. The punching shear failure is an undesirable failure mode, since it results in a brittle failure of the footing. In this study, a new method to increase the strength and ductility of the footing was proposed by inserting the punching shear preventers (PSPs) into the footing. The validation and effectiveness of PSP were verified through a series of experimental studies. The nonlinear finite element analysis was then performed to demonstrate the failure mechanism of the footing with PSPs in depth and to investigate the key parameters that affect the behavior of the footing with PSPs. Finally, the design recommendations for the footing with PSPs were suggested.